2021
DOI: 10.1016/j.jbc.2021.101267
|View full text |Cite
|
Sign up to set email alerts
|

Distinct conformers of amyloid beta accumulate in the neocortex of patients with rapidly progressive Alzheimer's disease

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 72 publications
1
39
0
Order By: Relevance
“…Both studies reported phenotypic variations associated with strain morphology. Phenotypic variations include variations in incubation time, symptoms, degree of pathology as well as affected regions and cell types representing various pathological profiles (Lau et al, 2020 ; Liu et al, 2021 ). These findings support the notion of specific asyn strains causing distinct disease phenotypes.…”
Section: Alpha-synuclein and Strain Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Both studies reported phenotypic variations associated with strain morphology. Phenotypic variations include variations in incubation time, symptoms, degree of pathology as well as affected regions and cell types representing various pathological profiles (Lau et al, 2020 ; Liu et al, 2021 ). These findings support the notion of specific asyn strains causing distinct disease phenotypes.…”
Section: Alpha-synuclein and Strain Variabilitymentioning
confidence: 99%
“…Thus, the distinct conformation or “spectral fingerprint” of the ligand upon interaction with a certain asyn aggregate reflect the 3D structure of that asyn aggregate (Klingstedt and Nilsson, 2012 ; Gustafsson et al, 2021 ). These fluorescent LCO-ligands thus identify a broader subset of pathogenic protein aggregates than conventional ligands such as ThT, as they have been established as a class of ligands for superior recognition and spectral assignment of disease-associated protein aggregates, including different polymorphic Aβ (Ellingsen et al, 2013 ; Rasmussen et al, 2017 ; Calvo-Rodriguez et al, 2019 ; Lantz et al, 2020 ; Liu et al, 2021 ), asyn (Klingstedt et al, 2019 ; Shahnawaz et al, 2020 ) aggregates, as well as toxic and non-toxic polymorphic variants of insulin, both in vitro (Psonka-Antonczyk et al, 2012 ; Mori et al, 2021 ) and in patient biopsies (Yuzu et al, 2020 ).…”
Section: Luminescent Conjugated Oligothiophenes To Identify Different...mentioning
confidence: 99%
See 1 more Smart Citation
“…To make a comparative conformational analysis of Aβ1–42 fibrils formed in the absence and presence of chaperones, we performed hyperspectral fluorescence microscopy analysis of fibrils incubated without ThT for 48 h and thereafter co-stained with the conformation sensitive luminescent conjugated oligothiophenes (LCOs) qFTAA and hFTAA ( Nyström et al, 2013 ; Rasmussen et al, 2017 ; Liu et al, 2021 ). Aβ1–42 fibrils formed in vitro are usually dominated by hFTAA fluorescence as is displayed by low ratio values in the ratio plot of qFTAA/hFTAA fluorescence ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the key points in protein aggregation diseases is the multitude of structures, known as polymorphism, that appear because of the plasticity of misfolded proteins. Hence, we hypothesized that this is an important mechanism for disease phenotype and refer to these diseases in plural, e.g., Alzheimer’s diseases ( Rasmussen et al, 2017 ; Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%